2017
DOI: 10.5687/iscie.30.459
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Phenomena in the Kaldor Business Cycle Model

Abstract: The periodic behavior of macroeconomic indicators or business cycles is a common observation in the economic system. In the past, business cycle modeling often involved the use of non-linear economic dynamic theory, general equilibrium theory, and methods to analyze complex systems, such as agent-based modeling and complex network theory. Several studies have shown that crisis and synchronization in business cycles can be modeled using threshold characteristics in the economic systems. In a non-linear system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Over decades, many types of synchronization phenomena in nonlinear systems have been explored (reviewed in 1–3 ). Among them, stochastic resonance, in which additive noise enhances the response to weak input signals, has been widely observed in nonlinear systems, such as global climate 4 , economic 5 , electric 6 , and biological 710 systems. In particular, regarding recent studies about stochastic resonance in neural systems, we reported that spike-timing-dependent plasticity might be enhanced by stochastic resonance, and the enhancement depends on neural spiking patterns 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Over decades, many types of synchronization phenomena in nonlinear systems have been explored (reviewed in 1–3 ). Among them, stochastic resonance, in which additive noise enhances the response to weak input signals, has been widely observed in nonlinear systems, such as global climate 4 , economic 5 , electric 6 , and biological 710 systems. In particular, regarding recent studies about stochastic resonance in neural systems, we reported that spike-timing-dependent plasticity might be enhanced by stochastic resonance, and the enhancement depends on neural spiking patterns 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a wide range of non-linear systems, it is known that additive stochastic noise and internal dynamical fluctuation enhance the ordering of spatio-temporal behaviors, such as the emergence of periodicity and synchronization (as reviewed in [1][2][3][4][5][6]). Among these phenomena, stochastic resonance is a phenomenon in which the effects of additive noise strengthen the signal response against weak input signals in the non-linear systems with a specific barrier or threshold [7][8][9] (as reviewed in [1,2,4,10,11]). Recent studies on stochastic resonance have been conducted considering various engineering applications, such as biomedical engineering [12,13], telecommunications [14], and memory storing mechanisms [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These nonlinear synchronization phenomena are classified according to the sources of fluctuation, i.e., additive stochastic noise and internal deterministic chaos. The former one is called stochastic resonance, which is observed in various kinds of systems, such as climate systems, nonlinear electric circuits, biological systems, and social systems [10]- [17]. The latter one is called chaotic resonance [18], [19], which is observed in systems with chaoschaos intermittency (CCI) where the chaotic orbit appears between separate regions, such as one-dimensional cubic map, Chua's circuit, Lorenz systems, and duffing systems [20], [21] (reviewed in [19], [22]- [24]).…”
Section: Introductionmentioning
confidence: 99%